Applying bagging techniques to the SA Tabu miner rule induction algorithm - CHorbev, Ivan; Andovska, Mirjana (Springer, Berlin, Heidelberg, 2009)
This paper presents an implementation of bagging techniques over the heuristic algorithm for induction of classification rules called SA Tabu Miner. The goal was to achieve better predictive accuracy of the derived classification rules. Bagging (Bootstrap aggregating) is an ensemble method that has attracted a lot of attention, both experimentally, since it behaves well on noisy datasets, and theoretically, because of its simplicity. It is directly related to bootstrap sampling, since it uses the bootstrap samples to train multiple predictors. The outputs of the predictors are then combined by various voting strategies. Bootstrap is a good solution when it is impossible, or too expensive, to get multiple samples. In this paper we present the experimental results of various bagging versions of the SA Tabu Miner algorithm. The SA Tabu Miner [1] algorithm is inspired by both research on heuristic optimization algorithms (Simulated Annealing and Tabu Search based Data Miner) and rule induction data mining concepts and principles. The algorithm creates rules incrementally, performing a sequential process to discover a list of classification rules covering as many as possible training cases with as big quality as possible. It uses a combination of Simulated Annealing and Tabu Search to perform the search for the optimal classification rule. Several bootstrap methodologies were applied to SA Tabu Miner, including reducing repetition of instances, forcing repetition of instances not to exceed two, using different percentages of the original basic training set. Various experimental approaches and parameters yielded different results on the compared datasets. In the paper we discuss the results and conclude that the best improvement in predictive accuracy was achieved by using only 10 voting classifiers derived from 90% of the basic training dataset.
Keywords: Bagging, Bootstrap, Simulated Annealing, SA Tabu Miner, Tabu Search, Data Mining, Rule Induction